Evaluation of smartphone addiction in students: a medical school example - İkiışık, Hatice and Turan, Güven and Korkmaz, Selin and Aydın, Hüseyin Bilal and Solak, Hatice Merve and Özmeral, Kübra and Bayram, Semanur and Bulut, Mücahit and Maral, Işıl (Journal of Dependence, 2020)
Objective: The aim of this study is to evaluate the relationship between the use of smartphones and individuals’ sociodemographic characteristics, personality characteristics and smart phone usage habits. Method: The students studying in a public medical faculty were tried to be reached. Besides a questionnaire to evaluate sociodemographic characteristics and smartphone usage habits, Smart Phone Addiction Scale Short Version (SAS-SV) and Big-Five personality dimensions instrument(BFI) were applied. Results: We reached 780 (84.7%) students. The social networks is the most common use purpose of the smartphone in 81.3% (n:634) of students. Women’s SAS score is higher than men with a score of 29.85 (± 10.35). According to the most used social media network, SAS score was found 31.58 (±10.80) in those with Instagram response. Conclusion: The use of the smartphone, which has become an integral part of the students’ life, has become a routine behavior of daily life. However, this behavior can turn into a potential addiction. It should be remembered that this addiction will have negative effects on the mental and physical health of the person and it should be ensured that awareness about the conscious and appropriate use of the smart phone should be provided.